Measures of mortality in the study of individuals infected with the human immunodeficiency virus in the UK haemophilia population - Darby, S; Ewart, D (1998)
Two statistical issues that have arisen in the course of a study of mortality and disease related to the human immunodeficiency virus (HIV) in the haemophilia population of the UK are discussed. The first of these concerns methods of standardization for age and it is shown that, when the mortality of HIV-infected individuals with different severities of haemophilia are compared, an analysis based on the ratio of observed to national expected deaths suggests that mortality in HIV-infected individuals depends on the severity of their haemophilia. This conclusion is inappropriate and mortality in HIV-infected individuals is, in fact, similar regardless of severity of haemophilia. The second part of the paper discusses the effect of using various end points for studies of survival and progression of HIV-related disease. In the present example it was possible to calculate relative survival in HIV-infected individuals, i.e. survival after correcting for mortality expected in the absence of HIV infection. An analysis based on absolute survival gave a very similar picture of the effect of age at infection to an analysis based on relative survival, whereas an analysis based on the time to diagnosis of acquired immune deficiency syndrome (AIDS) underestimated the effect substantially and the possible alternative end point of time to AIDS or HIV-related death was shown to be subject to considerable misclassification error.